Characteristics of voriconazole-induced visual disturbances and hallucinations: case reports and literature review - Liu, Ya; Huang, Ying; Liu, Xiang; Wang, Danxia; Hu, Yixiang (Frontiers in Pharmacology, 2024)
Voriconazole, a broad-spectrum antifungal agent, is considered the first-line treatment for invasive aspergillosis. In this article, we report three cases of patients who experienced visual disturbances and hallucinations following voriconazole therapy for invasive pulmonary aspergillosis. These symptoms appeared within one week after initiating voriconazole administration and resolved upon discontinuation or dose reduction of the drug. Considering the absence of any identifiable alternative cause and the temporal relationship with voriconazole initiation, these symptoms were attributed to the adverse effects of voriconazole. All three patients had trough concentrations exceeding 5 μg/mL at the time of adverse reactions, leading to subsequent therapeutic drug monitoring and dose adjustment. The clinical characteristics and management strategies of voriconazole-induced hallucinations and/or visual disturbances have been rarely reported previously. Therefore, our study reviewed and analyzed relevant case reports since 2014. This study highlights the importance of recognizing the potential risk of hallucinations and visual disturbances associated with voriconazole. Furthermore, our findings indicate that the route of voriconazole administration does not influence the frequency of these adverse events.Additionally, special attention should be given to monitoring adverse events related to voriconazole in Asian populations due to their higher prevalence of CYP2C19 poor metabolizers. In the event of adverse reactions to voriconazole, diligent monitoring of therapeutic drug levels and dosage adjustments is crucial. These clinical characteristics and management strategies offer advantages in terms of enhancing drug efficacy, ensuring treatment continuity, and minimizing the incidence of other severe adverse reactions.